Marseille, a land to the south of no north. The presence of criminal groups in the ville méditerranée (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
This paper aims to address the issue of the presence of criminal groups in Marseilles, from the years of the great migrations at the start of the last century, in which the Mediterranean port was the heart of commercial and cultural exchanges, up to more recent times, in which the city has brought its European profile to the fore, by building it. We will examine the issues and the personalities that emerge within the context as it changes from phase to phase throughout this period, along with the conceptualization of the phenomenon which is the Italian Mafia; this latter organization, as a litmus test, will enable us to grasp the characteristics of the Marseille milieu, its specific features, and what it has in common with the mafia, in both the logic and the wielding of its power. Marseilles, incarnating all the contradictions of the South, will set the stage for reflections on the factors which favor the birth and strengthen the growth of criminal groups. The intention, in addition to analyzing the single case of Marseille is, further, to show the extent to which France is still unprepared in the fight against organized crime of the mafia type, underestimating its effects, as well as the impelling need for European intervention on this issue to harmonize national legislations.